Identification and Functional Analysis of the Sex-Determiner Transformer-2 Homologue in the Freshwater Pearl Mussel, Hyriopsis cumingii - Wang, Yayu; Wang, Xiaoqiang; Ge, Jingyuan; Wang, Guiling; Li, Jiale (Frontiers in Physiology, 2021)
Transformer-2 (Tra-2) is an upstream regulatory element of the sex regulation mechanism in insects and plays a critical role in sex formation. To understand the role of tra-2 in Hyriopsis cumingii, the full-length Hctra-2 (1867bp) was obtained from the gonads, and sequence alignment with other species showed that HCTRA-2 protein had a highly conserved RRM domain. Phylogenetic analysis showed that the HCTRA-2 protein was a close relative to of the mollusks TRA-2 protein. The qRT-PCR of tissue-specific expression pattern showed that the Hctra-2 was abundant in gonads, and the expression in testes was higher than that in ovaries (P < 0.01). It suggests that Hctra-2 may play a potential regulatory role in gonadal development of H.cumingii; In the early gonadal development, the Hctra-2 expression was the highest on the third day after fertilization and increased slightly from 4 months to 5 months, which may be related to the embryonic sex determination and early gonadal development. In situ hybridization showed that Hctra-2 mRNA signals was present in both male and female gonads. After silencing Hctra-2 by RNAi, the expression levels of Hcfem-1b and Hcdmrt were changed. It is speculated that there may be a certain relationship between them, which plays an important role in the sex regulation of H.cumingii. Our research will help to deepen our understanding of the shellfish sex determination mechanisms.